1993
DOI: 10.1192/bjp.163.5.651
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Impact of HIV Infection in Gay Men, Drug Users and Heterosexuals

Abstract: The aim of this study was to establish the prevalence of current and past psychiatric morbidity in HIV seropositive asymptomatic subjects belonging to three transmission categories (gay men, intravenous drug users, and heterosexuals) compared with that found in HIV seronegative controls from the same groups. A cross-sectional, controlled study including 279 seropositive subjects belonging to groups II and III defined by the Center for Disease Control (94 gay men, 157 intravenous drug users, and 28 heterosexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 35 publications
3
17
1
1
Order By: Relevance
“…Reports of the lifetime prevalence of anxiety disorders among PLWH/A have ranged from 4% to 19% (Rabkin, 1996), which is somewhat lower than the general population estimates that range from 15% (Regier et al, 1990) to 25% (Kessler et al, 1994). Rates for adjustment disorders have generally been similar to those for anxiety disorders (Bialer et al, 1996;Dew et al, 1997;Gala et al, 1993;Lyketos et al, 1994;Rabkin, 1996).…”
Section: Prevalence Of Mental Disorders Among Plwh/amentioning
confidence: 84%
See 3 more Smart Citations
“…Reports of the lifetime prevalence of anxiety disorders among PLWH/A have ranged from 4% to 19% (Rabkin, 1996), which is somewhat lower than the general population estimates that range from 15% (Regier et al, 1990) to 25% (Kessler et al, 1994). Rates for adjustment disorders have generally been similar to those for anxiety disorders (Bialer et al, 1996;Dew et al, 1997;Gala et al, 1993;Lyketos et al, 1994;Rabkin, 1996).…”
Section: Prevalence Of Mental Disorders Among Plwh/amentioning
confidence: 84%
“…Rates for current anxiety disorders have likewise been highly variable, ranging from under 5% (Dew et al, 1997;Gala et al, 1993;Rabkin, 1996) to between 10% and 15% Brown et al, 1992;Rabkin et al, 1997a;Sewell et al, 2000), compared with general population estimates ranging from 13% (Regier et al, 1993) to 17% (Kessler et al, 1994). Among PLWH/A, social anxiety disorder and generalized anxiety disorder are the most common anxiety disorders encountered, unlike the general population, where social anxiety disorder and simple phobias are the two most common current anxiety disorders (Kessler et al, 1994).…”
Section: Prevalence Of Mental Disorders Among Plwh/amentioning
confidence: 92%
See 2 more Smart Citations
“…In fact, the IVDU population is at greater risk of psychopathology than HIV-seropositive heterosexuals, hemophiliacs, and gay men [78], and this population should be specially considered during treatment or the planning of treatment with forms of psychotherapy. Grassi et al [79] examined suicidal ideation and psychological morbidity in HIV-seropositive IVDUs compared with hepatitis C virus (HCV) IVDUs and found that suicide ideation, psychological morbidity, and anxiety and depression symptoms were not directly influenced by HIV serostatus.…”
Section: Psychotherapymentioning
confidence: 99%